Kapasitas Resin Immobilized Photocatalyst-Zno untuk Menyisihkan Total Nitrogen pada Limbah Dalam Reaktor Fotokatalis secara Continue - Nuriadin Kazal; Firra Rosariawari; Okik Hendriyanto Cahyonugroho; Aussie Amalia (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Nitrogen is one of the organic compounds contained in liquid waste produced by the tofu industry. In aquatic ecosystems, excessive amount of nitrogen can lead to eutrophication and increase the amount of ammonia, nitrate and nitrite which are poisonous to humans, livestock and wildlife. In order to deal with the issues, photo-catalyst technology is employed to process the organic liquid waste by converting themintoCO_2 and water which are relatively safer. Throughout the process, it requires a medium like resin immobilized photocatalyst-ZnO (RIP-ZnO) to absorb the pollutants. Based on the aforementioned background, this study aims to analyze the impact of RIP-ZnO capacity in reducing the total Nitrogen parameter. The analysis of total Ninthisstudy was conducted by using the Kjeldahl method consisting of three processes, namely destruction, distillation and titration. The research began with the process of making reactor and RIP-ZnO. Subsequently, once the total N concentration is known, the process of resin capacity calculation is continued. As a result, the research findings indicate that the highest resin capacity of 1.14542 reduces the total Nby 33%, while the lowest one of 0.00012 decreases it by 59%. In other words, the resin capacity has an impact on the percentage of total N removal. In conclusion, the lower the resin capacity is, the higher the removal percentage is, and vice versa.